Untersuchungen zur Bearbeitungsqualität im Fertigungssystem Laserstrahlschneiden - Nuss, Rudolf (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1989)
This research enlarged the knowledge concerning the quality determining influencing variables during laser beam cutting and to set the stage for an optimal process management and its realization. For the first time the significant interactions within the manufacturing system laser beam cutting were taken into account. This was possible by applying a specifically created laser beam- and process diagnostics system, which allowed to correlate local cut surface criteria with present process parameters and resulting surface properties. Taking into consideration the different geometrical elements a test workpiece was developed, on the basis of which it was possible to scientifically prove that, among other things, the achievable machining accuracy within the laser beam cutting enables the fabrication of finished part